The dysfunction of mission-oriented innovation policy: Impeding the accumulation of scientific knowledge in the Japanese academic sector - Takashi Hirao; Yusuke Hoshino (Administrative Sciences, 2024)
Since the Organisation for Economic Cooperation and Development presented its com- prehensive Innovation Strategy in 2010, numerous countries have been updating their innovation policies. Subsequent to the promulgation, the innovation policies of Japan shifted the focus from discipline-specific to social issue-oriented approaches. This study investigates the response of the Japanese academic sector to this policy shift and the characteristics of the research projects associated with innovation policy by utilizing descriptive statistics from policy documents and the database of Grants-in-Aid for Scientific Research. The findings reveal that Japanese researchers have increasingly aligned their efforts with government-proposed research themes in recent years, with a notable shift toward short-term research projects. Moreover, Japanese universities are undergoing reforms that are transforming them into entrepreneurial institutions by altering incentive structures. Although these reforms may yield short-term research outcomes, they may not always address long-term so- cietal needs. The narrowing focus on research themes could restrict the potential impact of research and impede the development of innovative solutions to societal challenges. From this viewpoint, assessing the relationship between government-proposed research themes and the research produc- tivity of Japan is critical. Universities and public research institutions play a vital social role in broad- ening the foundational knowledge base through basic research, while private enterprises may lack the motivation to invest in research and development with low appropriability. These results may be beneficial for policymakers in reconsidering the division of labor in industry-academic collaboration in a knowledge-intensive economy.
Keywords: 350; mission-oriented innovation policy; scientific knowledge; entrepreneurial university; academic sector; incentive structure